1996
DOI: 10.1093/infdis/173.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Combined Live Attenuated Measles, Mumps, Rubella, and Varicella Vaccine (MMRIIV) in Healthy Children

Abstract: An investigational tetravalent combined measles, mumps, rubella, and varicella vaccine and measles-mumps-rubella and varicella vaccines at separate injection sites given at the same visit were evaluated with respect to safety and cell-mediated and humoral immune responses at 6 weeks and 1 year after vaccination. Varicella seroconversion rates and lymphocyte proliferation responses were 100% for both vaccine groups at 6 weeks and 1 year. However, the antibody titer to varicella was lower in the combined vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Concomitant administration of MMR and varicella vaccines at separate injection sites has been shown to be well tolerated and to have no detrimental effects on the immunogenicity of any of the vaccine components [19,20]. Several attempts have been made to combine these vaccines, either as an extemporaneous mixture or as a tetravalent MMRV formulation but some of the feasibility studies have suggested that the immunogenicity of some antigens, especially varicella, may be affected by the combination [21][22][23][24]. Current formulations widely allowed to overcome these interactions [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant administration of MMR and varicella vaccines at separate injection sites has been shown to be well tolerated and to have no detrimental effects on the immunogenicity of any of the vaccine components [19,20]. Several attempts have been made to combine these vaccines, either as an extemporaneous mixture or as a tetravalent MMRV formulation but some of the feasibility studies have suggested that the immunogenicity of some antigens, especially varicella, may be affected by the combination [21][22][23][24]. Current formulations widely allowed to overcome these interactions [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Results from studies conducted with an early formulation of the Merck quadrivalent vaccine (MMRV) showed that the seroconversion rates and geometric mean titers (GMTs) to varicella-zoster virus (VZV) afforded by MMRV were lower than those after M-M-R ® II and VARIVAX ® administered concomitantly but at separate injection sites. 24,25 Therefore, MMRV was reformulated with a higher potency of VZV to yield ProQuad ® . ProQuad ® was first evaluated in a clinical study (Study 1) to determine whether the higher potency of the VZV component could overcome the decrease in VZV antibody response rates and GMTs that had been observed in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antibody titre to varicella was lower in the MMRV group at six weeks there was no diVerence between the groups at one year. There was no significant diVerence in lymphocyte proliferation responses between the groups 47 and no diVerences in the frequency of local and systemic reactions.…”
Section: Oka Strain Varicella Vaccine In Combination With Mmr Vaccinementioning
confidence: 77%